Genome-Wide Gene-by-Smoking Interaction Study of Chronic Obstructive Pulmonary Disease. Issue 5 (27th October 2020) - Kim, Woori; Prokopenko, Dmitry; Sakornsakolpat, Phuwanat; Hobbs, Brian D; Lutz, Sharon M; Hokanson, John E; Wain, Louise V; Melbourne, Carl A; Shrine, Nick; Tobin, Martin D; Silverman, Edwin K; Cho, Michael H; et al.
Abstract: Risk of chronic obstructive pulmonary disease (COPD) is determined by both cigarette smoking and genetic susceptibility, but little is known about gene-by-smoking interactions. We performed a genome-wide association analysis of 179, 689 controls and 21, 077 COPD cases from UK Biobank subjects of European ancestry recruited from 2006 to 2010, considering genetic main effects and gene-by-smoking interaction effects simultaneously (2-degrees-of-freedom (df) test) as well as interaction effects alone (1-df interaction test). We sought to replicate significant results in COPDGene (United States, 2008–2010) and SpiroMeta Consortium (multiple countries, 1947–2015) data. We considered 2 smoking variables: 1) ever/never and 2) current/noncurrent. In the 1-df test, we identified 1 genome-wide significant locus on 15q25.1 (cholinergic receptor nicotinic β4 subunit, or CHRNB4 ) for ever- and current smoking and identified PI * Z allele (rs28929474) of serpin family A member 1 ( SERPINA1 ) for ever-smoking and 3q26.2 (MDS1 and EVI1 complex locus, or MECOM ) for current smoking in an analysis of previously reported COPD loci. In the 2-df test, most of the significant signals were also significant for genetic marginal effects, aside from 16q22.1 (sphingomyelin phosphodiesterase 3, or SMPD3 ) and 19q13.2 (Egl-9 family hypoxia inducible factor 2, or EGLN2 ). The significant effects at 15q25.1 and 19q13.2 loci, both previously described in prior genome-wide association studies of COPD or smoking, were replicated in COPDGene and SpiroMeta. We identified interaction effects at previously reported COPD loci; however, we failed to identify novel susceptibility loci.